Evaluation of the solar cooling and heating system of the CUT mechanical engineering laboratories - Kalogirou, Soteris A.; Francou, Foivos; Florides, Georgios A. (My University, 2013)
The main objective of this paper is to describe and analyze the experimental system of solar cooling and heating, installed at the Mechanical Engineering laboratories of the Cyprus University of Technology (CUT). For this purpose, the behavior and performance of the system was studied over a period of one year, both for the cooling and heating modes using the Building Management System records. Furthermore, the performance of absorption chillers during the summer months was examined, and suggestions are made to reduce further the power consumption and to increase the overall efficiency of the system. The mean value of the coefficient of performance of the chiller was 0.68, which is quite high, even though the water entering the chiller was at a relatively low average temperature of 68°C. From the measurements it was also observed that there was excessive indirect energy consumption. Its main cause was related to the general pump over-sizing and the management of the un-used solar energy. Suggestions are given to reduce this consumption. The results of this study are very important because through our suggestions it is possible to increase efficiency, reduce energy consumption and make the system economically attractive to users.
Keywords: Absorption chillers; Coefficient of performance; Solar cooling